1990
DOI: 10.1056/nejm199011083231901
|View full text |Cite
|
Sign up to set email alerts
|

Regression of Coronary Artery Disease as a Result of Intensive Lipid-Lowering Therapy in Men with High Levels of Apolipoprotein B

Abstract: In men with coronary artery disease who were at high risk for cardiovascular events, intensive lipid-lowering therapy reduced the frequency of progression of coronary lesions, increased the frequency of regression, and reduced the incidence of cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
647
4
28

Year Published

1993
1993
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 2,031 publications
(700 citation statements)
references
References 48 publications
17
647
4
28
Order By: Relevance
“…Blood pressure reduction, HDLc elevation, apoC III distribution, Lp(a) levels, and compliance with lifestyle changes have also emerged in one or more studies. HARP [27], and CCAIT, [28], and CARE [29], call into question the merits of treating patients with more normal lipid levels, although CLAS [30] and FATS [31,32] support this approach. When women have been included in these studies [33,34] the arterial treatment benefits were comparable, or superior, to those of men.…”
Section: Promoting Lesion Regressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressure reduction, HDLc elevation, apoC III distribution, Lp(a) levels, and compliance with lifestyle changes have also emerged in one or more studies. HARP [27], and CCAIT, [28], and CARE [29], call into question the merits of treating patients with more normal lipid levels, although CLAS [30] and FATS [31,32] support this approach. When women have been included in these studies [33,34] the arterial treatment benefits were comparable, or superior, to those of men.…”
Section: Promoting Lesion Regressionmentioning
confidence: 99%
“…Indeed, this has been the case. In FATS [31], a 73 % reduction in clinical events was entirely explained by a 92 % reduction in the likelihood that mild or moderate coronary lesions would progress abruptly to severe stenosis and resulting severe ischemia. However, lesions severe ( 70 %S) at baseline did not appear to so benefit from lipidlowering.…”
Section: Prevention Of Plaque Disruptionmentioning
confidence: 99%
“…The incidence of myo pathy during monotherapy with statins is approxi mately 1 in 1000, although the combination with fibrates, cyclosporin, nicotinic acid and erythromycin might amplify this risk [54], In animal studies, treatment with HMG-CoA re ductase inhibitors has been shown to retard the de velopment of atherosclerosis [55,56]. Moreover, in tensive lipid lowering using HMG-CoA reductase inhibitors is the most effective in terms of inducing plaque regression and reducing the number of clini cal events in men with established CAD and PVD [18,19,25,28,[30][31][32][33][34][35][36][37][38][39][40][41]. Recently, a meta-analysis that pooled data from four studies treating men and women with 10-40 mg per day pravastatin for 2-3 years showed that a decrease in LDL-cholesterol of 28% from baseline was associated with a 62% reduc tion in the combined incidence of non-fatal and fatal myocardial infarction [57].…”
Section: Hmg-coa Reductase Inhibitorsmentioning
confidence: 99%
“…Lipid lowering therapy has conclusively demonstrated retardation in rate of progression of coronary arterial narrowing (angiographically proven) and reduction in size of atherosclerotic plaque in humans [2,3]. Scandinavian simvastatin survival study (4S) by demonstrating reduction in CAD and total mortality by 30% and 42% respectively, has established the value of lipid lowering by statins in CAD patients [4,5].…”
Section: Introductionmentioning
confidence: 99%